The storage of oil palm (Elaeis guineensis ) seed after high temperature treatment - Mok, Chak Kim; Hor, Yue Luan (International Seed Testing Association, 1977)
For rapid and maximal germination, the oil palm seed has to undergo a high temperature treatment. After the heat-treatment the seeds, if not germinated immediately, may be stored. The conditions an-d duration of storage have not been defined and were investigated in two experiments. The results show that '[iura' type seed after heat treatment can be stored at an initial 18% moisture content in an enclosed polythene bag. The duration of storage varied with the temperature. At 20°C and 28°C the seeds could be stored for 19 and 24 weeks respectively. At 30°C germination was impaired after ten weeks of storage. A rapid loss in seed moisture was recorded at the two higher temperatures. The low temperature of SoC caused an early decline in see? viability.